The Specific Morphological Features of Alveolar Bone. Issue 5 (July 2018) - Zhou, Siru; Yang, Yiling; Ha, Nayoung; Zhang, Peng; Ma, Xuhui; Gong, Xinyi; Hong, Yueyang; Yang, Xiao; Yang, Shuliang; Dai, Qinggang; Jiang, Lingyong
Abstract : Objective: The aim of the study was to study the specific morphological features of alveolar bone and compare it to femoral bone in rats. Methods: Twelve 3-month-old nonpregnant female Sprague–Dawley rats were used in the present study. The left maxillae and femurs of 6 rats were used for micro-computed tomography (micro-CT) scanning. The trabecular bone of the distal femur and the interradicular alveolar bone of the maxillary first molar were reconstructed and analyzed. Another 6 rats were used for histological analysis of trabecular bone and alveolar bone. Results: Micro-CT analysis suggested that the femoral trabecular bone was porous with rod-like trabeculae with a scattered distribution in bone marrow, whereas alveolar bone showed a compact structure with plate-like trabeculae and limited bone marrow. Tissue mineral density, bone mineral density, bone volume fraction, and trabecular thickness were dramatically higher in the alveolar bone compared with that in the trabecular bone. Alveolar bone displayed lower trabecular number and trabecular separation. Histomorphometric analysis showed that alveolar bone was formed of compact bone with wide trabeculae, whereas femurs were composed of loose bone with finer trabeculae. Conclusions: In comparison to the spongiosa of the distal femur, alveolar bone displays specific morphological features with compact, wide, and highly mineralized trabeculae.